Evolution or revolution: where next for impact assessment?. Issue 6 (2nd November 2018) - Banhalmi-Zakar, Zsuzsa; Gronow, Claire; Wilkinson, Lachlan; Jenkins, Bryan; Pope, Jenny; Squires, Geraldine; Witt, Kathy; Williams, Galina; Womersley, Jon
ABSTRACT: Impact assessment (IA) has become one of the most prevalent environmental policy instruments today. Its introduction under the National Environmental Policy Act (US) in 1969 was revolutionary. Perhaps it is not surprising, then, that such a widely used tool has received its share of criticism, including that it fails to meet some of its fundamental goals. Over the last fifty years, IA has broadened in scope and application and embraced new techniques. It has followed evolved, but has not changed fundamentally. We believe that IA must continue to change to meet the societal and environmental challenges of the 21 st century. But will it be enough for IA to progress through incremental change (evolution), or is a complete overhaul of impact assessment (revolution) needed? We provide some ideas as to what 'evolution' and 'revolution' may look like, but rather then offering a definitive way forward now, we invite stakeholders to present their thoughts and suggestions at the IAIA19 Annual Conference in Brisbane, which carries the same theme as the title of this article.